Analyzing Factors Influencing Stock Prices on Ex-Dividend Day: Insights into Dividend Yield, Investor Behavior, and Market Sentiment - Rio Dhika; Rina Dewi (Indonesia Accounting Research Journal, 2024)
This research investigates the factors influencing stock prices on ex-dividend day, offering insights into market dynamics and investor behavior. Through empirical analysis and comparison with theoretical expectations, the study examines the impact of dividend characteristics, trading volume, market sentiment, tax considerations, and company-specific factors on stock price movements surrounding the ex-dividend date. The findings highlight the significance of dividend size and yield, trading volume, and market sentiment in driving stock price adjustments on ex-dividend day. Additionally, the study explores the role of tax considerations and company-specific factors in shaping stock price dynamics, shedding light on the multifaceted nature of ex-dividend day trading. The implications of research findings for investors, financial markets, and future research are discussed, emphasizing the importance of informed decision-making, market efficiency, and continued exploration of market behavior on ex-dividend day.